DYNAMICS ANALYSIS OF ECONOMIC GROWTH, EXPORT, AND FOREIGN DIRECT INVESTMENT IN ASEAN : EMPIRICAL EVIDENCE FROM PANEL DATA ANALYSIS - MAHRUS LUTFI ADI KURNIAWAN; INDANAZULFA QURROTA A’YUN; LESTARI SUKARNIATI (LP2MTBM MAKARIOZ, 2021)
This study investigates the relationship between real GDP, real exports, and FDI inflows in 6 ASEAN countries from 2000 to2019. The purpose of this study is to construct strategies about export-led growth, growth-led export, FDI-led growth, andvice versa. Furthermore, the strategies can be applied by policymakers. The Granger causality panel approach revealed thatonly Vietnam has a two-way causality relationship between real GDP and real exports. Malaysia does not find a causalrelationship between real GDP and real exports, and for the rest, there is only a one-way relationship between real GDP andreal exports. This study employs the dynamic panel approach to examine the trivariate model: real GDP, real exports, andFDI inflows. The results show that the study found growth-led exports and growth-led FDI. This study implies that aneconomy fully supported by economic growth is sensitive to global dynamics and trade changes. Thus, it can affect exportactivities and the investment climate.